(untitled) (Hekima Review, 2016)
The image of the door has marked some important events since the opening of the Jubilee Year of Mercy. A door represents various actions. We open a door, we close it, we go through it, and people enter through a door. Opening a door is a task that can be easy, but at times difficult. The difficulty may come from the fear of the unknown, the stranger, the enemy. The apprehension of what we may encounter through the opening of the door hinges on our refusal to let others in. Which doors need to be opened? How far do we refuse to open them? Reflecting on the simple gesture of opening the door may lead us to reconsider and re-examine our attitudes as Christians or as believers.